Comments on the Ad Hoc Committee’s Critique of the Massachusetts Teacher Tests - Wainer, Howard (Education Policy Analysis Archives, 1999)
The critique of the Massachusetts Teacher Tests (MTT) by Haney and his colleagues is deserving of comment, both because of the impact of the MTT and because of the evocative manner in which the tale is told. Their emphasis on examples makes for a forceful argument, and I fear that my reliance on precepts may look meager by comparison. Nevertheless, I hope that some of the observations that follow contribute to the more reasoned assessment of these instruments and their use not just in Massachusetts but in the many other states where similar programs are being developed or contemplated.